ANALISIS POTENSI DESA DAN TANTANGAN DALAM MENINGKATKAN PERKEMBANGAN DAN PEMBANGUNAN DESA WOLWAL SELATAN - Maria Delia B. Tukan; Intan Permatasari Lema Madde; Musa Famau; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
Wolwal Selatan Village is one of the villages that has prominent advantages in terms of natural and social resources. However, this village still faces several development challenges, such as a poverty rate affecting more than one hundred households, low educational quality, limited infrastructure, environmental degradation, and the risk of natural disasters. This study aims to analyze the village’s potentials and problems as a guideline for formulating future village development recommendations. The research method used in this study is qualitative descriptive. The data were collected through observation, interviews, and documentation. The results show that although the community of Wolwal Selatan Village faces various challenges, the values of togetherness and mutual cooperation remain the main strengths supporting village development efforts. Natural beauty, local wisdom, and community productivity continue to serve as a strong foundation for developing the village to become more advanced and competitive. With proper management, these challenges can be transformed into opportunities to improve community welfare and optimize the village’s untapped potentials.